Literature Review on Islamic Educational Psychology and the Implementation of Its Theories in the World of Education - Suwarni Jayanti; Komarudin Evendi; Supriandi Supriandi (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This literature review explores the theoretical foundations of Islamic Educational Psychology and its practical implementation in contemporary educational settings. By integrating modern psychological theories with Islamic values derived from the Qur’an, Hadith, and classical as well as contemporary scholarly thought, Islamic Educational Psychology offers a holistic perspective on human development. The findings show that Islamic psychology emphasizes the balanced growth of the physical, intellectual, emotional, and spiritual dimensions of learners. This integrative perspective provides a more comprehensive alternative to secular psychological theories, which often overlook the spiritual dimension of human behavior. The review also highlights the relevance of Islamic Educational Psychology in addressing modern educational challenges such as moral degradation, stress, and identity crises among students. Its implementation through the roles of teachers as murabbi, value-infused curricula, motivational frameworks based on sincerity and worship, and spiritually oriented therapeutic practices proves effective in strengthening students’ character, motivation, and psychological well-being. This study concludes that Islamic Educational Psychology plays a crucial role in shaping holistic educational practices that produce intellectually competent, emotionally stable, and spiritually grounded individuals.